2015
DOI: 10.24266/0738-2898-33.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Blueberry Culture and Pest, Disease, and Abiotic Disorder Management during Nursery Production in the Southeastern U.S.: A Review

Abstract: The genus Vaccinium represents an increasingly important group of plants for the U.S. green industry. In 2012, blueberries (Vaccinium sp.) ranked the second most important berry crop in the U.S. with a total crop value over $780 million. The popularity of blueberries creates opportunities as well as challenges for nursery crop producers. This article presents a review of current nursery production practices of blueberry and explores the challenges and opportunities for nursery crop producers, including pestici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 57 publications
0
7
0
2
Order By: Relevance
“…This result indicated that almost no blueberry fruits were damaged by SWD in conventional and intelligent spray plots. Blueberry fruit is susceptible to SWD, with yield of blueberry reduced by 30% to 100% in untreated plots (Fulcher et al, 2015). Few SWD were found in 2019 in the black raspberry plots.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This result indicated that almost no blueberry fruits were damaged by SWD in conventional and intelligent spray plots. Blueberry fruit is susceptible to SWD, with yield of blueberry reduced by 30% to 100% in untreated plots (Fulcher et al, 2015). Few SWD were found in 2019 in the black raspberry plots.…”
Section: Resultsmentioning
confidence: 99%
“…In the United States, codling moth (Cydia pomonella) is the most serious pest in apple fruit (Beckerman, 2018), and oriental fruit moth (Grapholita molesta) is one of the most damaging pests in peach fruit (Brunner and Rice, 1993). Spotted wing drosophila (Drosophila suzukii) has been a serious pest of blueberry and black raspberry over the past 10 years (Fulcher et al, 2015). Potato leafhopper (Empoasca fabae) is a severe pest of maple trees in the Eastern United States (Frank et al, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…En cambio, los necrótrofos se desarrollan en el tejido muerto de la planta o pueden causar la muerte de ésta, ya que no pueden absorber los nutrientes (Muñoz, 2008). El género Vaccinium posee frutos climatéricos que maduran con rapidez y que son susceptibles a enfermedades causadas principalmente por hongos como Neofusicoccum y Phomopsis (Cruañes & Locaso, 2011;Fulcher et al, 2015). Una de las enfermedades más conocidas del género Vaccinium es la roya, generada por Hemileia vastatrix, que se presenta en la primavera con una incidencia que puede llegar hasta el 84,39%; se caracteriza por generar la caída de las hojas y antracnosis en el tallo.…”
Section: Microorganismos Patógenos Que Afectan Al Género Vacciniumunclassified
“…Estos hongos tuvieron menor incidencia en plantas cuando fueron colocadas en cuarto frío (Figueroa et al, 2010). A su vez, se ha detectado Phytophthora cinnamomi y P. citrophthora en el arándano (Fulcher et al, 2015), ocasiona la pudrición de la raíz y reduce su desarrollo entre 36,5 y 53,4%; afectando el tamaño del tallo (Larach et al, 2009).…”
Section: Microorganismos Patógenos Que Afectan Al Género Vacciniumunclassified